2005
DOI: 10.1002/j.1556-6678.2005.tb00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Suicide by Teenagers in Middle School: A Postvention Team Approach

Abstract: This article was prompted by a recent suicide by a middle school child. The school counselor who was involved (the sixth author) related the following experience. One Child's SuicideAs a helping professional working in public education for 5 years, I have dreaded confronting a few types of situations. One early fear I had was discovering and reporting child abuse. However, there was nothing I dreaded more than the possibility of dealing with a child's suicide. Unfortunately, I was tested by this challenge duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…(2000) showed that the unsolicited mass distribution of information and materials related to suicide and violence prevention is of limited usefulness. Maples (2005) described the corrections made to a suicide crisis management intervention to avoid romanticizing suicide. Callahan (1996) described how a sense of "specialness" and secrecy served to heighten students' sense of melodrama over a school mate's suicide, which also furthered the spread of suicide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2000) showed that the unsolicited mass distribution of information and materials related to suicide and violence prevention is of limited usefulness. Maples (2005) described the corrections made to a suicide crisis management intervention to avoid romanticizing suicide. Callahan (1996) described how a sense of "specialness" and secrecy served to heighten students' sense of melodrama over a school mate's suicide, which also furthered the spread of suicide.…”
Section: Resultsmentioning
confidence: 99%
“…(Ryerson, 1990) The approach could be adapted to include the prevention and intervention phases of dealing with teen suicides. (Maples et al, 2005)…”
Section: Data Availabilitymentioning
confidence: 99%
“…The current solution‐focused applications also speak to recent research that has found that families who have lost a loved one to suicide have significant resiliency (Clark & Goldney, 1995; Davis & Nolen‐Hoeksema, 2001; Kaslow & Aronson, 2004; Murphy et al., 2003). In contrast to prevailing treatment approaches that are largely cognitive‐behavioral and psychoeducational (e.g., Dunne & Dunne‐Maxim, 2004; Forde & Devaney, 2006; Juhnke & Shoffner, 1999; Kubany, 1998; Maples et al., 2005; Roberts et al., 1998), solution‐focused therapy highlights families’ existing or potential resources and emphasizes the resiliency of families coping with suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Kubany (1998) has developed a cognitive-behavioral model that includes techniques for helping family members identify and dispute erroneous thinking. Maples et al (2005) have described a team approach involving counselors, administrators, parents, and teachers following the suicide of a middle school child using a four-stage model developed by Roberts et al (1998). Juhnke and Shoffner (1999) have described a critical incident stress debriefing model for families that incorporates solution-focused techniques.…”
Section: Suicide and Familiesmentioning
confidence: 99%
See 1 more Smart Citation